The international dictionary of heating, ventilating and air conditioning (E & FN Spon, 1994)
The Dictionary is divided into two sections. The main sequence of the book consists of some 4,000 terms given in English, in alphabetical order, with their translations. The remainder of the book consists of alphabetical indexes for the other eleven languages covered: French, German, Italian, Danish, Finnish, Dutch, Spanish, Swedish, Hungarian, Polish and Russian. Each alphabetical index is keyed to serial numbers which refer the user to the correct item in the main sequence.